Equinoideos del miembro calcáreo superior, formación tibasosa, en el área de firavitoba (boyacá - colombia). morfología y fauna asociada (2002)
There is a relevant occurrence of equinoid fossils into the Upper Calcareous Member of the Tibasosa Formation with early Hauterivian (?) to late Aptian age according to ammonites.  Heteraster cesarensis COOKE, were reported in the formation. But to Pseudocidaris cf. clunifera (AGASSIZ), Phymosoma sp., Holectypus (Coenholectypus) cf. planatus (ROEMER), Globator cf. parryi (HALL), Phyllobrisus cf. angostatus (CLARK), Arnaudaster colombianus COOKE and Douvillaster? sp., are the first record to the Tibasosa Formation.